Partially absorbable sports medicine orthopedic suture line and preparation method thereof

By using sports medicine orthopedic sutures made of polylactic acid and polyglycolic acid composites, adding biologically active ingredients and designing shape memory alloys and porous structures, the problem that sutures cannot adapt to dynamic changes in tissues under the physiological environment is solved, achieving efficient tissue healing and reducing the risk of postoperative infection.

CN119524186APending Publication Date: 2025-02-28周滢
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411630927.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing sutures cannot effectively adapt to the dynamic changes in tissues under the physiological environment, resulting in uneven tension during suture, affecting the healing effect, and have shortcomings in cell adhesion and antibacterial properties, which cannot effectively prevent postoperative infection.

Method used

Partially made of composite materials of polylactic acid and polyhydroxyacetic acid can absorb sports medicine orthopedic sutures, add bioactive ingredients such as bone morphogenetic proteins, silver nanoparticles and hydroxyapatite, and improve the mechanical properties, biocompatibility and antibacterial properties of sutures through shape memory alloys and porous structure design, combined with low-temperature plasma treatment and chemical grafting treatment, to improve the mechanical properties, biocompatibility and antibacterial properties of sutures.

Benefits of technology

It realizes that sutures are automatically adjusted in shape under physiological conditions, adapt to dynamic changes in tissues, provide uniform tension and support, and promote tissue healing; it improves cell adhesion and antibacterial properties, reduces postoperative infection risk, shortens healing time, and ensures the stability and durability of sutures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524186A_ABST
    Figure CN119524186A_ABST
Patent Text Reader

Abstract

The invention relates to the field of biomedical textile materials, and discloses a partially absorbable sports medicine orthopedic suture line and a preparation method thereof.The suture line is prepared from, by mass, 50%-90% of polylactic acid and 10%-20% of polyglycolic acid. The mass content of polyglycolic acid is 10%-50%, the composite material further comprises a bioactive component, the mass content of the bioactive component is 0.1%-10%, the bioactive component comprises bone morphogenetic protein, silver nanoparticles and hydroxyapatite, the tensile strength of the suture line is 30-120 MPa, and under different physiological conditions, the suture line is not prone to fracture, and the suture line is not prone to fracture. And the degradation product can be compatible with surrounding tissues. The shape of the suture line can be automatically adjusted at the physiological temperature by embedding the shape memory alloy, and the suture line can adapt to dynamic changes of the tissue and provide uniform tension and support when interacting with the biological tissue due to the intelligent response capability, so that the tissue healing is effectively promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical textile materials, in particular to partially absorbable sports medicine orthopedic sutures and a preparation method thereof. Background Art

[0002] With the continuous advancement of medical technology, the requirements for suture materials in the fields of sports medicine and orthopedics are getting higher and higher. Traditional suture materials usually use non-absorbable polymers such as nylon or polyester. These materials need to be removed through a secondary operation after surgery, which increases the burden on patients and the risk of postoperative complications. At the same time, although some absorbable sutures can gradually degrade in the body, their mechanical properties and biocompatibility often cannot meet the needs of complex tissue healing.

[0003] In recent years, researchers have begun to explore composite materials that can have excellent mechanical properties while ensuring biocompatibility. Among them, polylactic acid and polyglycolic acid, as biodegradable polymers, have gradually attracted attention due to their excellent biocompatibility and absorbability. However, sutures made of a single material still have deficiencies in strength, degradation rate and bioactivity, so research on composite materials has gradually emerged.

[0004] At present, although various types of sutures have been widely used in the existing technology, most products still have certain shortcomings. Many sutures cannot effectively adapt to the dynamic changes of tissues under physiological conditions, resulting in uneven tension during the suturing process, which in turn affects the healing effect. At the same time, the improvement of existing suture materials in terms of cell adhesion ability and antibacterial properties is still limited, and it cannot effectively prevent postoperative infection, increasing the risk of recovery for patients. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a partially absorbable sports medicine orthopedic suture and a preparation method thereof, which solves the problem that the prior suture cannot effectively adapt to the dynamic changes of tissues under physiological conditions, resulting in uneven tension during the suturing process.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a partially absorbable sports medicine orthopedic suture comprises the following components:

[0007] The suture is made of a composite material of polylactic acid and polyglycolic acid, wherein the mass content of polylactic acid is 50% to 90%, the mass content of polyglycolic acid is 10% to 50%, and the composite material also contains bioactive components, the mass content of the bioactive components is 0.1% to 10%, and the bioactive components include bone morphogenetic protein, silver nanoparticles and hydroxyapatite.

[0008] Preferably, the tensile strength of the suture is 30-120 MPa, and its degradation products are compatible with surrounding tissues under different physiological conditions. The diameter of the suture is 200-600 μm.

[0009] Preferably, the surface of the suture is coated with a bioactive coating, the coating is composed of polyvinyl alcohol and polyglycolic acid, and the thickness of the coating ranges from 5 to 15 μm.

[0010] A method for preparing partially absorbable sports medicine orthopedic sutures comprises the following steps:

[0011] Step 1: melt-blending polylactic acid and polyglycolic acid in a mass ratio of 70:30 and 60:40, controlling the melting temperature of the mixture at 160-190 degrees, and stirring at this temperature for 30-60 minutes to ensure that the material is fully melted;

[0012] Step 2: Processing the melted composite material into sutures by extrusion or electrospinning, wherein the diameter of the sutures is controlled to be 200-600 μm;

[0013] Step 3, cooling the suture at room temperature to form a desired suture substrate;

[0014] Step 4: using an aerosol spray method to evenly coat the bioactive components such as bone morphogenetic protein and silver nanoparticles on the surface of the suture, and drying at ambient temperature for 12-24 hours after coating;

[0015] Step 5: Finally, the coated suture thread is treated with low-temperature plasma to improve its surface hydrophilicity. The treatment time is 1 to 10 minutes.

[0016] Preferably, in step 1, during the extrusion process of the melt-blended material, the uniform diameter of the suture thread is achieved by controlling the extrusion rate and temperature, the extrusion rate is 0.5-5 kg / h, and the temperature is 160-190 degrees.

[0017] Preferably, the internal structure of the suture is a porous structure with a porosity of 10% to 50%. The porous structure is used to promote the penetration of biological fluids and the growth of cells.

[0018] Preferably, a shape memory alloy is embedded in the suture, and the alloy can be restored to a preset shape at physiological temperature and has a shape memory effect, and the phase transition temperature of the alloy is 30-40 degrees.

[0019] Preferably, the surface of the suture is treated with low-temperature plasma to increase its hydrophilicity and surface energy, and the treatment time is 1 to 10 minutes to achieve predetermined surface characteristics.

[0020] Preferably, the biocompatibility of the suture is improved by chemical grafting treatment, the grafted polymer is selected from polyvinyl alcohol, polyvinyl alcohol-polyvinyl ether copolymer and polymethacrylic acid, and the grafting treatment step includes dissolving the polymer in an organic solvent and reacting with the surface of the suture to enhance the surface activity of the suture.

[0021] Preferably, the suture can be used for suturing soft tissue or hard tissue, and is suitable for sports medicine and orthopedic surgery.

[0022] The present invention provides a partially absorbable sports medicine orthopedic suture and a preparation method thereof.

[0023] Beneficial effects:

[0024] 1. The present invention embeds shape memory alloys in sutures, which can automatically adjust their shapes at physiological temperatures. This intelligent response capability enables the sutures to adapt to the dynamic changes of tissues when interacting with biological tissues, provide uniform tension and support, and thus effectively promote tissue healing.

[0025] 2. The porous structure design and surface modification of the suture of the present invention improve the cell attachment ability, which is conducive to the rapid proliferation and migration of cells. Such optimization promotes the tissue regeneration process, especially in the early stage of healing, provides a good growth environment for cells and shortens the healing time.

[0026] 3. The present invention combines bioactive ingredients (such as silver nanoparticles and bone morphogenetic protein) to give the suture a certain antibacterial effect. This property effectively reduces the risk of postoperative infection, ensures the cleanliness and safety of the surgical site, and helps improve the patient's recovery efficiency.

[0027] 4. The present invention takes into account the porous structure and shape memory effect while maintaining good tensile strength through the suture thread, ensuring stability and durability during use. This superior mechanical property provides a reliable guarantee for the suture effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] Please refer to the attached Figure 1 The embodiment of the present invention provides a partially absorbable sports medicine orthopedic suture, comprising the following components:

[0032] The suture is made of a composite material of polylactic acid and polyglycolic acid, wherein the mass content of polylactic acid is 50% to 90%, the mass content of polyglycolic acid is 10% to 50%, and the composite material also contains bioactive components, the mass content of the bioactive components is 0.1% to 10%, and the bioactive components include bone morphogenetic protein, silver nanoparticles and hydroxyapatite.

[0033] The tensile strength of the suture is 30-120 MPa, and its degradation products are compatible with the surrounding tissues under different physiological conditions. The diameter of the suture is 200-600 μm.

[0034] The surface of the suture is coated with a bioactive coating composed of polyvinyl alcohol and polyglycolic acid, and the thickness of the coating ranges from 5 to 15 μm.

[0035] In one embodiment, the partially absorbable sports medicine orthopedic suture of this embodiment is made of a composite material of polylactic acid and polyglycolic acid, the mass content of polylactic acid is set to 70%, and the mass content of polyglycolic acid is 30%. The composite material is prepared by melt blending, ensuring good compatibility and uniformity of the two polymer materials.

[0036] The bioactive ingredients added to the material include bone morphogenetic protein (BMP-2), silver nanoparticles and hydroxyapatite, with a mass content of 5%. These bioactive ingredients can not only promote cell growth and tissue regeneration, but also enhance the antibacterial properties of sutures and reduce the risk of postoperative infection.

[0037] The tensile strength of the suture is set at 80MPa, which ensures the stability and safety of the suture during the suturing process. The diameter of the suture is 300μm, which is suitable for the needs of most sports medicine and orthopedic surgeries. Under physiological conditions, the degradation products of the suture are compatible with the surrounding tissues, and the degradation time can be controlled within 6 months, avoiding postoperative foreign body reactions.

[0038] In addition, the suture surface is coated with a bioactive coating of polyvinyl alcohol and polyglycolic acid with a thickness of 10 μm. This coating is designed to further improve the biocompatibility of the suture, promote cell attachment and growth, and provide additional bioactive support.

[0039] Embodiment 2:

[0040] Please refer to the attached Figure 1, a method for preparing a partially absorbable sports medicine orthopedic suture comprises the following steps:

[0041] Step 1: melt-blending polylactic acid and polyglycolic acid in a mass ratio of 70:30 and 60:40, controlling the melting temperature of the mixture at 160-190 degrees, and stirring at this temperature for 30-60 minutes to ensure that the material is fully melted;

[0042] Step 2: Processing the melted composite material into sutures by extrusion or electrospinning, wherein the diameter of the sutures is controlled to be 200-600 μm;

[0043] Step 3, cooling the suture thread at room temperature to form the desired suture thread substrate;

[0044] Step 4: using an aerosol spray method to evenly coat the bioactive components such as bone morphogenetic protein and silver nanoparticles on the surface of the suture, and drying at ambient temperature for 12-24 hours after coating;

[0045] Step 5: Finally, the coated suture thread is treated with low-temperature plasma to improve its surface hydrophilicity. The treatment time is 1 to 10 minutes.

[0046] In one embodiment, in this embodiment, polylactic acid and polyglycolic acid are first weighed at a mass ratio of 70:30. This ratio is selected to balance the mechanical strength and absorbability of the suture and ensure the good performance of the final product in a physiological environment. The weighed PLA and polyglycolic acid mixture is placed in a twin-screw extruder.

[0047] In the extruder, the melt temperature of the mixture needs to be strictly controlled between 170 and 190 degrees to ensure that the material is fully melted and to avoid degradation of the material due to excessive temperature. The screw speed is set to 100-150RPM and the stirring time is 40 minutes to promote the mutual dissolution and uniform mixing of polylactic acid and polyglycolic acid. During this process, cross-linking of the molecular chains of polylactic acid and polyglycolic acid will begin to occur, forming a stable composite material and improving the overall performance of the suture.

[0048] In one embodiment, in this embodiment, the molten polylactic acid and polyglycolic acid composite material is processed into suture thread by extrusion. During the extrusion process, the temperature of the mixture is set to 180 degrees to ensure sufficient fluidity and uniformity of the material. The screw speed of the extruder is set to 120RPM to ensure that the mixture can be fully and evenly formed when passing through the extrusion die.

[0049] The diameter of the suture after forming is strictly controlled at 400μm. In order to ensure the uniformity and stability of the suture, a quantitative feeding system is used during the extrusion process to ensure the consistency of the feeding amount each time. At the same time, the extruded suture is quickly cooled by a cooling water tank to fix its shape and prevent deformation.

[0050] The resulting sutures are collected after cooling and are cut and trimmed as necessary to prepare for subsequent steps. This process ensures the uniformity and maneuverability of the sutures, making them suitable for applications in sports medicine and orthopedic surgery.

[0051] Through such a melt blending process, the final composite material not only has good mechanical properties, but also ensures the smooth progress of subsequent processing. The successful implementation of this link lays a solid foundation for the preparation of sutures, allowing subsequent molding and coating processes to proceed smoothly, thereby achieving ideal product performance.

[0052] In one embodiment, in this embodiment, the suture obtained after melt extrusion immediately enters the cooling water tank. The temperature of the cooling water tank is set to room temperature (about 25 degrees), and the suture is immersed in the water tank for 2 minutes to ensure that the suture is quickly cooled and solidified. Through this rapid cooling method, the molecular structure of the suture is quickly fixed to avoid shape deformation or performance degradation caused by temperature changes.

[0053] After cooling is completed, the suture is pulled out of the water tank by a mechanical device and the surface is cleaned to remove moisture and impurities that may be attached during the cooling process. Finally, the suture is collected after sorting and is ready to enter the subsequent coating and processing steps.

[0054] This process effectively ensures the operability and consistency of the suture in subsequent processes, thereby laying a good foundation for subsequent bioactive ingredient coating and surface treatment.

[0055] In one embodiment, in this embodiment, an aerosol spray method is used to uniformly coat the bioactive ingredients on the surface of the cooled suture, and the bioactive ingredients used include bone morphogenetic protein and silver nanoparticles. In the specific operation, the bone morphogenetic protein is dissolved in physiological saline to maintain its concentration at 1 mg / mL, and the concentration of the silver nanoparticles is set to 50 ppm.

[0056] The pressure of the spraying process was set at 0.5 MPa, and the distance between the nozzle and the suture was maintained at 10 cm to ensure uniform coating. The suture moved at a speed of 5 cm per minute during the spraying process to ensure uniform adhesion of the bioactive ingredients. After coating, the suture was placed in a room temperature environment for drying for 18 hours to ensure that the bioactive ingredients were firmly attached to the suture surface.

[0057] The sutures treated through this process have good biological activity, which helps promote cell adhesion and proliferation after implantation and creates good conditions for tissue healing. The successful implementation of this link provides the necessary foundation for subsequent surface treatment steps.

[0058] In one embodiment, in this embodiment, the suture coated with the bioactive ingredient is first placed in a low-temperature plasma treatment device. During the treatment, the vacuum degree of the equipment is adjusted to 0.1 pressure to ensure good plasma generation and uniform treatment effect. The treatment time is set to 5 minutes to ensure sufficient surface activation without affecting the overall structure and performance of the suture.

[0059] During the treatment process, argon is used as the plasma gas to optimize the hydrophilicity of the suture surface. After the treatment, the suture is quickly removed and left at room temperature for 1 hour to allow the surface reaction to stabilize. This process ensures that the suture has good biocompatibility when used, which helps its effectiveness in subsequent clinical applications.

[0060] Through the implementation of this step, the surface properties of the suture are significantly improved, providing better conditions for subsequent biomedical applications.

[0061] In step 1, during the extrusion process of the melt-blended material, the uniform diameter of the suture thread is achieved by controlling the extrusion rate and temperature. The extrusion rate is 0.5-5 kg / h and the temperature is 160-190 degrees.

[0062] In one embodiment, in this embodiment, step one involves melt blending polylactic acid (PLA) and polyglycolic acid (PGA) to form a composite material with excellent mechanical properties and biocompatibility. During the extrusion process, the melt temperature of the material is set to 180 degrees to ensure that the polymer is fully dissolved and evenly mixed, and the extrusion rate is set to 2kg / h to ensure a stable supply of the material.

[0063] The diameter of the suture was maintained at 300 μm by precisely controlling the temperature and rate during the extrusion process, which not only requires the material to have good fluidity at high temperatures, but also to avoid polymer degradation caused by overheating. The interaction between polylactic acid (PLA) and polyglycolic acid (PGA) forms a uniform composite material at this stage, improving its physical properties and achieving the best balance between mechanical properties and biocompatibility of the final product.

[0064] The internal structure of the suture is a porous structure with a porosity of 10% to 50%. The porous structure is used to promote the penetration of biological fluids and the growth of cells.

[0065] In one embodiment, the presence of pores allows biological fluids to better penetrate into the interior of the suture, which is essential for promoting cell infiltration and growth. Cells enter the suture through these pores, interact with surrounding tissues, and promote the healing process. In addition, the porous structure helps to reduce the density of the suture, reduce the discomfort of the postoperative tissue, and improve the overall biocompatibility.

[0066] Shape memory alloy is embedded in the suture, which can restore to the preset shape at physiological temperature and has shape memory effect. The phase transition temperature of the alloy is 30-40 degrees.

[0067] In one embodiment, a shape memory alloy is embedded in the suture, and the phase transition temperature of the alloy is 35°C. This shape memory alloy can return to its preset shape at physiological temperature (about 37°C) and has an excellent shape memory effect. The shape memory alloy undergoes a specific heat treatment during the manufacturing process, so that it has the ability to achieve shape change when the temperature changes.

[0068] When the suture is implanted in the body, the shape memory alloy automatically changes to a preset shape after the temperature reaches the phase transition temperature. This feature enables the suture to better adapt to physiological conditions during the healing process, providing more uniform pressure distribution and support, thereby helping to accelerate tissue healing.

[0069] The surface of the suture is treated by low-temperature plasma to increase its hydrophilicity and surface energy. The treatment time is 1 to 10 minutes to achieve predetermined surface characteristics.

[0070] In one embodiment, the low-temperature plasma treatment of the suture surface is intended to increase its hydrophilicity and surface energy, thereby improving its biocompatibility. During the treatment process, the suture is placed in a low-temperature plasma device, and the treatment time is set to 5 minutes. During this process, the vacuum degree of the device is adjusted to 0.1 pressure, and argon is used as the plasma gas.

[0071] The generation of low-temperature plasma ionizes gas molecules to form charged particles, free radicals and excited molecules. These high-energy particles can effectively remove surface impurities and introduce hydrophilic functional groups (such as hydroxyl and carboxyl groups) when interacting with the suture surface. This surface modification not only increases the surface roughness, but also significantly increases the surface energy, which enhances the cell adhesion ability of the suture in vivo.

[0072] The biocompatibility of the suture is improved by chemical grafting treatment, the grafted polymer is selected from polyvinyl alcohol, polyvinyl alcohol-polyvinyl ether copolymer and polymethacrylic acid, and the grafting treatment step includes dissolving the polymer in an organic solvent and reacting with the surface of the suture to enhance the surface activity of the suture.

[0073] Sutures can be used to close soft or hard tissue and are suitable for sports medicine and orthopedic surgery.

[0074] In one embodiment, the biocompatibility of the suture is improved by chemical grafting. The grafted polymer used includes polyvinyl alcohol (PVA), polyvinyl alcohol-polyvinyl ether copolymer (PVA-PEO) and polymethacrylic acid (PMAA), and the grafting process is as follows:

[0075] Polymer dissolution: First, the selected polymer is dissolved in a suitable organic solvent (such as ethanol) at a mass concentration of 5% to form a uniform polymer solution.

[0076] Surface reaction: The suture is immersed in the polymer solution and the reaction time is set to 30 minutes. During this process, the polymer molecules combine with the surface of the suture through chemical reaction or physical adsorption to form covalent bonds or hydrogen bonds, thereby forming a modified film on the surface of the suture.

[0077] Washing and Drying: After the grafting reaction was completed, the suture was taken out and washed with deionized water to remove the unreacted polymer, and then dried at room temperature for 12 h to ensure the firmness and stability of the grafted layer.

[0078] The grafting process enhances the surface activity of the suture, making it more compatible in the biological environment.

[0079] In a preferred embodiment, the multi-layer composite suture

[0080] In this preferred embodiment, the suture adopts a multi-layer composite structure design, which is specifically composed of an inner layer and an outer layer. The inner layer material is a composite material of polylactic acid (PLA) and polyglycolic acid (PHA) with a mass ratio of 70:30. This combination not only provides good biocompatibility and mechanical strength, but also has a suitable degradation rate to ensure lasting support during the healing process. The outer layer is a chemically grafted polyvinyl alcohol (PVA) coating, and the thickness after treatment is controlled at 5-10μm, which significantly enhances the hydrophilicity and surface activity of the suture.

[0081] Through this multi-layer design, the inner layer provides the necessary strength and support to ensure the stability of the suture during surgery, while the hydrophilicity and activity of the outer layer help promote cell attachment and growth, thereby accelerating tissue healing. In addition, the polyvinyl alcohol coating on the outer layer can also absorb biological fluids to form a lubricating layer to reduce postoperative discomfort. This preferred embodiment is particularly suitable for soft tissue sutures that require rapid healing and complex orthopedic surgeries, providing more comprehensive clinical effects.

[0082] In a preferred embodiment, in this preferred embodiment, the surface of the suture is subjected to multifunctionalization treatment, combining chemical grafting and bioactive coating technology to enhance its biological performance and antibacterial properties. First, polyvinyl alcohol (PVA), polyvinyl alcohol-polyvinyl ether copolymer (PVA-PEO) and polymethacrylic acid (PMAA) are chemically grafted to enhance the hydrophilicity and cell adhesion of the suture.

[0083] Secondly, after the grafting treatment, a bioactive coating is applied to the surface of the suture, the main components of which are bone morphogenetic protein (BMP) and silver nanoparticles. The thickness of the coating is controlled at 10-15μm, which can effectively release BMP, stimulate cell proliferation and differentiation of surrounding tissues, and promote bone tissue regeneration. The introduction of silver nanoparticles enhances the antibacterial properties of the suture and reduces the risk of postoperative infection.

[0084] In addition, the design of the bioactive coating takes into account the stability and sustained release characteristics under physiological conditions, ensuring that it continues to work throughout the healing process. This preferred embodiment is particularly suitable for orthopedic surgery and complex soft tissue repair, significantly enhancing the clinical application value of sutures and improving patients' postoperative recovery experience.

[0085] Embodiment one:

[0086] Material selection: polycaprolactone or polylactic acid;

[0087] Preparation method:

[0088] Melt spinning: The polymer is heated to a molten state, passed through a spinneret to form fibers, and then stretched to increase strength and toughness.

[0089] Solution spinning: The polymer is dissolved in an appropriate solvent and nanofibers are prepared by techniques such as electrospinning to increase the surface area and bioactivity.

[0090] 3D printing: Using additive manufacturing technology, suture structures with specific shapes and mechanical properties can be designed and printed.

[0091] 1. Experimental Design

[0092] In order to verify the superiority of the partially absorbable sports medicine orthopedic suture proposed in Example 1, the following comparative experiment was conducted:

[0093] Comparison Materials:

[0094] Embodiment 1: Polylactic acid (PLA) and polyglycolic acid (PHA) composite suture.

[0095] Comparative Sample A: Polycaprolactone (PCL) suture.

[0096] Comparative sample B: pure polylactic acid suture (PLA).

[0097] Experimental indicators:

[0098] Tensile strength (MPa);

[0099] Degradation rate (months);

[0100] Biocompatibility (cell proliferation rate);

[0101] Antibacterial properties (inhibition zone diameter).

[0102]

[0103]

[0104] Table 1

[0105] Tensile strength: The tensile strength of Example 1 is 80 MPa, which is significantly higher than that of Comparative Samples A and B. This indicates that Example 1 has better mechanical stability during the suturing process, can withstand greater tension, and reduces the risk of suture breakage.

[0106] Degradation rate: The degradation time of Example 1 is 6 months, which is suitable for the healing period of sports medicine and orthopedic surgery. The degradation time of comparative sample A is too long, which may cause postoperative foreign body reaction; although the degradation time of comparative sample B is shorter, it lacks strong mechanical support.

[0107] Biocompatibility: The cell proliferation rate of Example 1 is as high as 90%, indicating that it has good compatibility with the organism, can effectively promote cell adhesion and proliferation, and contribute to rapid healing. In contrast, the biocompatibility of samples A and B is relatively low, which may limit their clinical application.

[0108] Antibacterial performance: Example 1 has outstanding antibacterial performance, with an inhibition zone diameter of 15 mm, indicating that it has a good inhibitory effect on bacteria. This property is particularly important and can reduce the risk of postoperative infection, while the antibacterial performance of samples A and B is obviously insufficient.

[0109] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A partially absorbable sports medicine orthopedic suture, characterized in that: Includes the following components: The suture is made of a composite material of polylactic acid and polyglycolic acid, wherein the mass content of polylactic acid is 50% to 90%, the mass content of polyglycolic acid is 10% to 50%, and the composite material also contains bioactive components, the mass content of the bioactive components is 0.1% to 10%, and the bioactive components include bone morphogenetic protein, silver nanoparticles and hydroxyapatite.

2. The partially absorbable sports medicine orthopedic suture according to claim 1, characterized in that: The tensile strength of the suture is 30-120 MPa, and under different physiological conditions, its degradation products are compatible with surrounding tissues. The diameter of the suture is 200-600 μm.

3. The partially absorbable sports medicine orthopedic suture according to claim 1, characterized in that: The surface of the suture is coated with a bioactive coating, which is composed of polyvinyl alcohol and polyglycolic acid, and the thickness of the coating ranges from 5 to 15 μm.

4. A method for preparing a partially absorbable sports medicine orthopedic suture, according to the partially absorbable sports medicine orthopedic suture according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: melt-blending polylactic acid and polyglycolic acid in a mass ratio of 70:30 and 60:40, controlling the melting temperature of the mixture at 160-190 degrees, and stirring at this temperature for 30-60 minutes to ensure that the material is fully melted; Step 2: Processing the melted composite material into a suture by extrusion or electrospinning, wherein the diameter of the suture is controlled to be 200-600 μm; Step 3, cooling the suture at room temperature to form a desired suture substrate; Step 4: using an aerosol spray method to evenly coat the bioactive components such as bone morphogenetic protein and silver nanoparticles on the surface of the suture, and drying at ambient temperature for 12-24 hours after coating; Step 5: Finally, the coated suture thread is treated with low-temperature plasma to improve its surface hydrophilicity. The treatment time is 1 to 10 minutes.

5. The method for preparing a partially absorbable sports medicine orthopedic suture according to claim 4, characterized in that: In the step 1, during the extrusion process of the melt-blended material, the uniform diameter of the suture thread is achieved by controlling the extrusion rate and temperature, the extrusion rate is 0.5-5 kg / h, and the temperature is 160-190 degrees.

6. The method for preparing a partially absorbable sports medicine orthopedic suture according to claim 4, characterized in that: The internal structure of the suture is a porous structure with a porosity of 10% to 50%. The porous structure is used to promote the penetration of biological fluids and the growth of cells.

7. The method for preparing a partially absorbable sports medicine orthopedic suture according to claim 4, characterized in that: The suture is embedded with a shape memory alloy, which can be restored to a preset shape at physiological temperature and has a shape memory effect. The phase transition temperature of the alloy is 30-40 degrees.

8. The method for preparing a partially absorbable sports medicine orthopedic suture according to claim 4, characterized in that: The surface of the suture is treated with low-temperature plasma to increase its hydrophilicity and surface energy. The treatment time is 1 to 10 minutes to achieve predetermined surface characteristics.

9. The method for preparing a partially absorbable sports medicine orthopedic suture according to claim 4, characterized in that: The biocompatibility of the suture is improved by chemical grafting treatment, wherein the grafted polymer is selected from polyvinyl alcohol, polyvinyl alcohol-polyvinyl ether copolymer and polymethacrylic acid, and the grafting treatment step includes dissolving the polymer in an organic solvent and reacting with the surface of the suture to enhance the surface activity of the suture.

10. The method for preparing a partially absorbable sports medicine orthopedic suture according to claim 4, characterized in that: The suture thread can be used for suturing soft tissue or hard tissue, and is suitable for sports medicine and orthopedic surgery.

Citation Information

Cited By

  • Calcium stearate modified PGA fiber for bone healing and preparation method thereof

    CN121629553A

  • An intelligent braided material with wet-pH dual response characteristics and a preparation method and application thereof

    CN122707315A